Gamma irradiation-assisted degradation of rosmarinic acid and evaluation of structures and anti-adipogenic properties. (30th August 2018) - Han Jeong, Gyeong; Cho, Jae-Hyeon; Jo, Cheorun; Lee, Sungbeom; Sik Lee, Seung; Bai, Hyoung-Woo; Chung, Byung Yeoup; Hoon Kim, Tae
Highlights: Degradation of rosmarinic acid was accelerated in methanol solution induced by gamma ray. The structures of new degraded compounds from rosmarinic acid were elucidated by extensive spectroscopic interpretation. Newly generated degraded products by gamma ray exposure can contribute to the enhancement of anti-adipogenic properties. A plausible degradation mechanism of rosmarinic acid by gamma irradiation was tentatively proposed. Abstract: Radiation is a promising technique for improving the safety and shelf-life of processed foods. In the present investigation, the degradation mechanism and bioactivity improvement of rosmarinic acid (RA) were studied in response to various gamma irradiation doses (10, 20, and 50 kGy). RA exposed to gamma irradiation at 50 kGy was completely degraded and showed an increased inhibitory effect against 3 T3-L1 preadipocyte compare to the parent compound. Structures of the newly generated compounds2 –4 from irradiated RA at 50 kGy were elucidated based on spectroscopic methods, including 1 H nuclear magnetic resonance (NMR) and mass spectrometry (MS). Interestingly, compounds2 and5 exhibited significantly enhanced anti-adipogenic properties in 3 T3-L1 cells compared to the original compound. These results provide evidence that structural changes in RA induced by gamma irradiation might enhance biological efficacy.